Borderland Regional Identity: The Case of the Klaipėda Region - Šutinienė, Irena (Sociologija. Mintis ir veiksmas, 2018)
[only abstract in English; full article and abstract in Lithuanian]This article examines the ways in which regional identity of the local residents of the Klaipėda region, who define themselves as Klaipėdiškiai (Memellanders), is constructed. The use of different symbolic resources in constructing symbolic boundaries of regional identity in different contexts and interactions are analyzed on the basis of the qualitative empirical research data – family histories collected in the Klaipėda region in 2016–2017. The transformations and the continuity of regional and ethnic identity of the locals in the contexts of suppression of their culture and identity during the Soviet regime are also discussed. The specific features of borderland identity, reconstructed in the case of the Klaipėda region’s population, are compared with the local Polish ethnic community living in another Lithuanian borderland territory – the Vilnius region.
Keywords: regional identity, ethnic identity, borderland, Klaipėda region